Ursula K. Le Guin - Spivack, Charlotte (Boston : Twayne Publishers, 1984)
Presents the life and works of Ursula K. Le Guin, author of fantasy and science fiction.
Includes index.
Bibliography: p. 173-177.
Young Adult.
Keywords: Le Guin, Ursula K., -- 1929- -- Criticism and interpretation